Pt/Al2O3Catalyzed Decolorization of Rhodamine B Dye in Aqueous Medium - Muhammad Saeed (Science Faculty of Chiang Mai University, 2019)
In this study 5% Pt supported on alumina (Pt/Al2O3) was used as catalyst for decolorization of Rhodamine B dye in aqueous medium in an agitated slurry batch reactor. Influence of different reaction parameters like temperature, time of reaction, speed of agitation, catalyst dose and initial concentration of Rhodamine B dye on decolorization was investigated. About 60-80% decolorization was noted in 120 minutes at temperature 303-323K. 550-908 were observed as turnover frequencies (TOF) for 100-300 ppm solution of Rhodamine B dye. Catalyst was tested for re-usability. It was found that fresh and used catalyst has almost same catalytic performance. The decolorization reaction followed the Langmuir-Hinshelwood type of mechanism, where adsorption of Rhodamine B at surface of catalyst followed Freundlich adsorption isotherm. Curve Expert software was used for kinetic analyses of the experimental data.15.36kJmol-1, 20.14 kJmol-1, -5.7 kJmol-1, 34.12 jmol-1 and -4.59 kJmol-1 were determined as apparent activation energy, true activation energy, enthalpy of adsorption, entropy and Gibbs free energy respectively.